Windows 11 for seniors - Simmons, Curt 1968- (John Wiley & Sons, Inc., 2025)
The top-selling Windows book for the older and wiser crowd Windows 11 For Seniors For Dummies, 2nd Edition delivers fluff-free information on making the latest version of Windows work for you. You'll get clear guidance on the basics, troubleshooting tips, and advice for staying safe while you use Windows to get online. Even if you've never used Windows before, this friendly guide will quickly teach you how to get started, without all the jargon and complicated steps. These simple steps and solutions give you the confidence boost you need to navigate the latest interface and even try out the artificial intelligence tools built into Windows. With larger print and clearer graphics, this For Seniors title saves you time and energy as you learn your way around your Windows computer. Get started with the latest version of Windows--without a lot of unnecessary jargon Communicate with friends, keep track of files, share photos and videos, and stream your favorite media Try out Copilot, the Windows AI tool that offers fast answers to any question Be your own tech guru with step-by-step troubleshooting and maintenance advice These days, a new computer or a new Windows update shouldn't have to slow you down. Spend less time learning and more time doing, with this edition of Windows For Seniors For Dummies.
Includes index
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Computers and older people; Systèmes d'exploitation (Ordinateurs); Ordinateurs et personnes âgées; operating systems